Analysis of Inputs in the Sexually Transmitted Infection Screening with Voluntary Counselling and Testing Program for Female Prisoners at Class II A Jail, in Malang - Rosyidah Alfitri; Argyo Demartoto; Eti Poncorini Pamungkasari (Journal of Epidemiology and Public Health, 2016)
Background: The increasing incidences of Sexually Transmitted Infection (STI) and Human Immonodeficiency Virus (HIV) infection are becoming serious public health concerns in Indonesia and other countries. These issues are of concern  that call for close attention not only for general public but also for male and female prisoners. As studies have shown the prevalences of HIV and syphilis were 1.1% and 5.1% in male prisoners, respectively, 6% and 8.5% in female prisoners. For those reasons,  at some  jails  Voluntary Counseling and Testing (VCT) have been provided  for HIV/AIDS control and prevention. The success of the screening program with VCT would depend on  the provision of supplies, equipment, infrastructure, health personnel, and fund. This study aimed to analyze the adequacy of various inputs in the STI screening program with VCT for prisoners at the Class II A female jail, in Malang, East Java.Subjects and Method: This was a qualitative study with evaluation approach. This study was conducted at the Class II A female jail, in Malang, East Java. The study applied CIPP (Context, Input, Process, Product) evaluation model. Key informants for this study included health personnels at the Class II A female jail clinics, in Malang, East Java, the STI mobile health care team from Arjuno Community Health Center Malang, and female prisoners, who were known as Warga Binaan Pemasyarakatan (WBP)Results: Average monthly visits at the VCT clinic were 21 female prisoners, which amounted to only a few of the total number of female prisoners. The health care team involved in the STI screening with VCT program, included skilled health personnel from the jail and the mobile STI team from Arjuno Community Health Center, Malang. The sources of fund for these programs came from the international as well as domestic funding agencies. The international funding came from the Global Fund. The domestic funding came from the Ministry of Law and Human Civil Rights, and the Municipality Health Office Malang, which provided reagents and medicine. Supplies, equipments, and infrastructure, were provided by Arjuno Community Health Center Malang and the Class II A female jail clinics, in Malang. The laboratory was provided by the health center. The reagents were sufficiently provided by the municipality health office, although there was a supply delay in February 2016.Conclusion: Inputs of the STI screening with VCT program at the Class II A female jail clinics, in Malang, East Java, which included supplies, equipment, infrastructure, health personnel, and funding, are sufficiently provided.    Keywords: analysis, input, screening, STI, VCTCorrespondence: Rosyidah Alfitri. Diploma III School of Midwifery, Dr. Soepraoen Hospital, Malang. Email: elfitri.mafaza@gmail.com.Journal of Epidemiology and Public Health (2016), 1(2): 118-124https://doi.org/10.26911/jepublichealth.2016.01.02.05